If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*x-4)/4 = (4*x-2)/6 // - (4*x-2)/6
(3*x-4)/4-((4*x-2)/6) = 0
(3*x-4)/4+(-1*(4*x-2))/6 = 0
(6*(3*x-4))/(4*6)+(-1*4*(4*x-2))/(4*6) = 0
6*(3*x-4)-1*4*(4*x-2) = 0
2*x-16 = 0
(2*x-16)/(4*6) = 0
(2*x-16)/(4*6) = 0 // * 4*6
2*x-16 = 0
2*x-16 = 0 // + 16
2*x = 16 // : 2
x = 16/2
x = 8
x = 8
| 2x+x=28 | | -3x+15=6x | | X+2X=85 | | 86.20= | | u=(x+1)(1-y) | | 2+7x=9+3x+2 | | y=0.2x+6.2 | | sinx/cosx=y | | ydx=dy | | 2x*-1x-1*-1=0 | | 2x*-1*x*-1=0 | | 98=x*8+2 | | 3x+2=23-4x | | 130+40+x=360 | | 3x-1/7=5 | | px+8=3 | | 2x=58m | | f(6)=13x+1 | | 12x=9-6 | | 3cos3(3pi/2) | | sen(3x)-sen(5x)=0 | | 8x+6x=29 | | 21x^2+150x=1000 | | 8x+11=63 | | -4p-7=-5+8p | | 6/5х=3/5 | | x+3x=-28 | | 3-x=-16 | | x=6(y+3) | | x=6*4y | | y+3=z+6 | | x*(x+1)*(x+2)*(x+3)=35 |